2020
DOI: 10.1038/s41598-020-70848-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific microRNAs in women with diabetes and left ventricular diastolic dysfunction or HFpEF associate with microvascular injury

Abstract: Left ventricular diastolic dysfunction (LVDD) and heart failure with preserved ejection fraction (HFpEF) are microcirculation defects following diabetes mellitus (DM). Unrecognized HFpEF is more prevalent in women with diabetes compared to men with diabetes and therefore sex-specific diagnostic strategies are needed. Previously, we demonstrated altered plasma miRs in DM patients with microvascular injury [defined by elevated plasma Angiopoietin-2 (Ang-2) levels]. This study hypothesized the presence of sex-dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…Still, in women, we previously demonstrated increased circulating levels of miR-224/452 in contrast to no significant effects in the transmen cohort ( Fig. 1G and H ) ( 43 ).…”
Section: Discussionmentioning
confidence: 68%
“…Still, in women, we previously demonstrated increased circulating levels of miR-224/452 in contrast to no significant effects in the transmen cohort ( Fig. 1G and H ) ( 43 ).…”
Section: Discussionmentioning
confidence: 68%
“…Last but not least research demonstrates that the sex-specific expression level of miRNA could be analyzed together with other markers to indicate diabetes complications. Heart failure with preserved ejection fraction (HFpEF) is an example of diabetes microvascular complications that have more prevalence in women and are frequently undiagnosed at the early stage of development (Florijn et al 2020). Interestingly, the elevated expression level of a protein marker of microvascular injury angiopoietin-2 (Ang-2) only in diabetic females with HFpEF along with lower expression levels of miR-224 and miR-452 in diabetic males with HFpEF (Florijn et al 2020) shows their potential to serve as sex-biased biomarkers.…”
Section: Sex Difference In Circulating Mirna In Dm2mentioning
confidence: 99%
“…Heart failure with preserved ejection fraction (HFpEF) is an example of diabetes microvascular complications that have more prevalence in women and are frequently undiagnosed at the early stage of development (Florijn et al 2020). Interestingly, the elevated expression level of a protein marker of microvascular injury angiopoietin-2 (Ang-2) only in diabetic females with HFpEF along with lower expression levels of miR-224 and miR-452 in diabetic males with HFpEF (Florijn et al 2020) shows their potential to serve as sex-biased biomarkers. In summary, all the mentioned results demonstrate the need for the development of sex-specific diagnostic strategies in diabetes mellitus type 2, as well as show the possibility of using circulating miRNAs as sex-biased biomarkers.…”
Section: Sex Difference In Circulating Mirna In Dm2mentioning
confidence: 99%
“…Previously, we reviewed the question of whether these mechanisms result in sex-specific microRNA expression within female microvascular cells [ 31 ]. We subsequently demonstrated that their sex-specific expression instigates a different clinical outcome in women compared to men, such as a higher prevalence of microvascular injury (defined by elevated angiopoietin-2 levels) following diabetes mellitus [ 32 ]. Lastly, we described the regulatory role of angiogenic microRNAs in cerebral small vessel disease [ 33 ].…”
Section: Introductionmentioning
confidence: 99%